APLICABILIDADE DA NORMA DE DESEMPENHO EM HABITAÇÃO POPULAR: ESTUDO DE CASO - Viana, Marina Ribeiro; Santos, Paulo Ricardo Ramos; Michelan, Denise Conceição de Gois Santos; Santos, Débora de Gois (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
NBR 15575 presents a set of requirements and criteria which make it possible to assess quantitatively and qualitatively the performance of a building. The research analyzed the applicability of performance standard (NBR 15575) in an enterprise of the program My House My Life. The method of work consisted of exploratory research with the establishment of a list for project and in site checks. This tool was applied in a case study in order to analyze the edification's situation regarding the enforcement with NBR 15575. As a result, it was found that for design, the item of fire safety obtained a higher percentage of checks satisfied. Already for inspection in the field, the item of functionality and accessibility was the most approval. Lighting performance was not in accordance with any of the aspects analyzed in the enterprise. It is concluded that the performance standard criteria are not being met fully, as one of the main obstacles conducts the test that are not part of the construction practices of the companies. Finally, it is expected that this paper can contribute to future studies on the topic and helps the construction companies in the adequacy of their enterprises to new regulatory requirements.